Code Choices Used by the Society in the Event of Halal Bi Halal Tradition: An ethnographic Study in Boyolali 2019 - haryanto, sigit; Fatmawati, Rini (Jurusan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2020)
Language, culture, and society are three things that cannot be separated. The intertwining among them are reflected in halal bi halal tradition. This annually tradition mainly uses Javanese language as a main central of social communication. Two common codes that used by the participants in conducting the event are krama and ngoko. The participants when choosing the codes, of course, are influenced by the social factors. Dealing with this, the aim of this study is finding the language choices use and the factors that affect the participants selecting the codes. This ethnographic study used participant observation in collecting the data. Then, the collected data were analyzed by theory of social dimension proposed by Holmes. The results of the study showed that (1) the language choices use are (a) Javanese krama, (b) Javanese ngoko, (c) mixture of Javanese and Arabic, (d) mixture of Javanese, and Arabic, and Indonesian, and (e) Indonesian and Indonesian and (2) the factors that affect the language choices are (a) the social relationship of the participants, (b) the setting of the event, (c) the formality of the vent, and (d0 the function for the event. As a conclusion, code choices that happen in halal bi halal tradition are commonly affected by social factor or nonlinguistic factor.